The experience of an antimicrobial stewardship program and antibiotic consumption and resistance trends during the COVID-19 pandemic at a tertiary care center in Beirut - Nisrine Haddad; Rony M. Zeenny; Celia El Halabi; Tamara Abdallah; Remie El Helou; Nada Kara Zahreddine; Souha S. Kanj; Nesrine A. Rizk (Journal of Infection and Public Health, 2024)
Background: Antimicrobial Resistance, a global concern, worsened with the COVID-19 pandemic that caused a surge of critically ill patients, increased antimicrobial consumption, and the spread of infections with multidrug-resistant organisms (MDROs). Antimicrobial Stewardship Programs (ASP) aim to optimize antimicrobial utilization to fight resistance. We aim to describe the ASP experience and to study antimicrobial consumption and MDRO rates among COVID-19 patients at a tertiary care center in Beirut. Methods: We compiled the ASP interventions, defined as ASP team recommendations, from January 2019 until December 2021. Data on antimicrobial consumption, expressed as a defined daily dose (DDD) per 100 patient days, was collected per quarter for all antimicrobials and restricted antimicrobials per ASP guidance. Our primary objective was to report on the ASP experience, and the secondary objective was to reflect on the rates of MDROs among hospitalized COVID-19 patients with respiratory or bloodstream bacterial co-infections between March 2020 and September 2021. Results: 9922 ASP interventions were documented during this study period, with a noticeable correlation between COVID-19 surges in Lebanon and the number of ASP interventions. Acceptance rates for these recommendations improved over time, with a noticeable decrease in the proportion of interventions related to de-escalation and discontinuation of broad-spectrum antimicrobials. We noted an increase in all antimicrobial consumption after the onset of the pandemic, peaking in Q4 2020 (142.8 DDD of anti-infectives/100 patient days) and Q1 2021 (79.1 DDD of restricted anti-infectives/100 patient days). As expected, MDROs, particularly ESKAPE organisms (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Carbapenem-resistant Enterobacteriaceae) accounted for 24% of isolates obtained from this cohort. Conclusion: This study highlights the experience of the ASP as we adapted to the COVID-19 pandemic. The ASP team maintained its operations and continued to monitor antibiotic consumption and provide recommendations to limit antibiotic misuse in an effort to mitigate the impact of the pandemic on antimicrobial resistance.